STUDI TENTANG KEPUASAN PELANGGAN DALAM SISTEM MANAJEMEN PENDIDIKAN ISLAM DI SMK MA’ARIF NU 1 PURBOLINGGO LAMPUNG TIMUR - Suparno, Suparno (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
This study is aimed to explain and predict factors influencing customer satisfaction in SMK Ma'arif NU 1 Purbolinggo East Lampung. Quality standards used as basic determiner of customer satisfaction are education national standard, those are: content standard, process standard, facilities standard, funding standard, and service standard. This study examines skill program quality, academic service quality, product and funding quality. Validity data in qualitative method was collected by interview, documentation, and observation. Then respondents of this study are researcher, headmaster, vice headmaster, teachers, parents, and students. Result of the study showed: First, the skill program is appropriate with content standard. Second, Academic service is appropriate with service standard so it has big contribution to the customer satisfaction. Analysis result of TERRA model Tangibelity, Empaty, Responsiveness, Reliability, and Assurance. Third, Product quality is supported by S1 qualified teachers, and sufficient facilities so it creates qualified academic product. It is also appropriate with process standard. Fourth Funding standard. The headmaster follows the valid rules in allocating funding standard those are arranging RAPBS, holding investigation, and holding the funding report by enclosing supported proof (receipt, and bill). Funding system impacts in creating education program, and improving academic service and product quality.